2007
DOI: 10.1037/0021-843x.116.4.701
|View full text |Cite
|
Sign up to set email alerts
|

A taxometric analysis of the latent structure of psychopathy: Evidence for dimensionality.

Abstract: The taxonomic status of psychopathy is controversial. Whereas some studies have found evidence that psychopathy, at least its antisocial component, is distributed as a taxon, others have found that both major components of psychopathy-callousness/unemotionality and impulsivity/antisocial behavior-appear to distribute as dimensions and show little evidence of taxonicity. In the present study, recent advances in taxometric analysis were added to P. Meehl's (1995) multiple consistency tests strategy for assessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
224
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 316 publications
(249 citation statements)
references
References 141 publications
20
224
1
4
Order By: Relevance
“…These results contrast sharply with studies that found dimensionality underlying psychopathy, ASPD, and CD (Edens et al, , 2011Guay et al, 2007;Murrie et al, 2007;Walters, 2009;Walters et al, 2007aWalters et al, , 2007bWalters et al, , 2007cWalters et al, , 2008. This discrepancy may refl ect reliance on adult inmate or juvenile detention center samples in prior studies that overrepresented individuals with severe antisocial syndromes.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…These results contrast sharply with studies that found dimensionality underlying psychopathy, ASPD, and CD (Edens et al, , 2011Guay et al, 2007;Murrie et al, 2007;Walters, 2009;Walters et al, 2007aWalters et al, , 2007bWalters et al, , 2007cWalters et al, , 2008. This discrepancy may refl ect reliance on adult inmate or juvenile detention center samples in prior studies that overrepresented individuals with severe antisocial syndromes.…”
Section: Discussioncontrasting
confidence: 56%
“…Several clinical rating scales designed to assess psychopathy have been used in taxometric research, including various versions of the Psychopathology Checklist (PCL) and its revisions, the PCL-Revised and the PCL-Antisocial Process Screening Device (Frick and Hare, 2001;Hare 1993), antisocial subscales of the Personality Assessment Interview (Morey, 2007), and the Levenson Self-Report Psychopathology Scale (Levenson et al, 1995). Within this tradition, eight studies conducted among adult jail and/or prison inmates (Dana, 1990;Edens et al, 2006;Guay et al, 2007;Marcus et al, 2004;Walters, 2009;Walters et al, 2007aWalters et al, , 2007bWalters et al, , 2007cWalters et al, , 2008 and two studies (Edens et al, 2011;Murrie et al, 2007) conducted among adolescents in juvenile correctional facilities consistently yielded evidence of dimensionality of psychopathy.…”
mentioning
confidence: 99%
“…Both the PCL-R (Guay, Ruscio, Knight, & Hare, 2007) and the PCL: SV (Walters, Gray, Jackson, Sewell, Rogers, Taylor, et al, 2007) measure a dimensional construct, and our primary analyses therefore involved correlations between the PCL: SV (and its factors) and its correlates, including demographic characteristics, verbal intelligence, DSM-IV Axis-II personality disorder traits, ICD-10 clinical syndromes, and social and behavioral problems. In addition, however, the PCL-R and PCL: SV scores can be used to provide convenient threshold or cut-scores for psychopathy, thereby allowing estimates to be made of the prevalence of the disorder in our sample.…”
Section: Introductionmentioning
confidence: 99%
“…However, given that psychopathy appears to be a construct that is continuously distributed (e.g., Guay, Ruscio, Knight, & Hare, 2007;Marcus, John, & Edens, 2004), one may reasonably expect some uniformity of PPI factor solutions across nonincarcerated and incarcerated populations. Moreover, other psychopathy research has found similar factor structures across very diverse samples (Hare & Neumann, in press).…”
mentioning
confidence: 99%